The influence of one-time biofeedback electromyography session on the firing order in the pelvic floor muscle contraction in pregnant woman–A randomized controlled trial - Błudnicka, Monika; Piernicka, Magdalena; Kortas, Jakub; Bojar, Damian; Duda-Biernacka, Barbara; Szumilewicz, Anna (Frontiers in Human Neuroscience, 2022)
Many women are initially unable to contract the pelvic floor muscles (PFM) properly, activating other muscle groups before, or instead of, PFM. Numerous authors have proved that biofeedback can be an ideal tool supporting learning of the PFM contraction. However, there is currently a lack of scientific data on how many biofeedback sessions are necessary in this educational process. In this study we aimed at assessing the effects of one-time electromyography (EMG) biofeedback session on the order in which PFM are activated (so called firing order) during conscious contractions in relation to selected synergistic muscles in pregnant, continent women. A randomized controlled trial was conducted in 90 healthy nulliparous women with uncomplicated pregnancies and without diagnosed urinary incontinence. We divided the participants into a biofeedback group (50) and a control group (40).Surface electromyography with vaginal probes has been used to assess the PFM firing order in selected tasks: in five 3-s maximal contractions (quick flicks), five 10-s contractions, and in a 60-s contraction (static hold). We used the 1-5 scale, where “1” meant the best score, awarded when PFM was activated first in order. The most important finding of our study is that a single EMG biofeedback substantially improved the PFM contractions in pregnant women. First, when applying one-time biofeedback session, more women maintained correct technique or improved it in the second assessment, compared to the control group (73 vs. 65 %). Secondly, using the quantitative and qualitative analysis with the Chi-square McNemara B/C test, in the biofeedback group we observed a statistically significant improvement of PFM firing order in 4 tasks: in the first quick flicks (p = 0.016), third quick flicks (p = 0.027), fifth quick flicks (p = 0.008) and in the first 10-second contractions (p = 0.046). In the control group we observed better outcome only in one motor task: in the fourth 10-second contraction (p = 0.009). Given the positive effects of a single session of EMG biofeedback on the firing order in the PFM contractions, it should be recommended for pregnant women without urinary incontinence to teach them how to perform PFM exercises correctly.